ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN MODEL SIX SIGMA DALAM PROSES PRODUKSI TALI PADA PT XYZ - Safri Safri; Herny Nurhayati; Iswandir Iswandir (JURNAL MITRA MANAJEMEN, 2023)
This study was conducted to manage raw material inventories based on defectives using the Six Sigma DMAIC (Define, Measure, Analyze, Improve, Control) methodology. Suggestions for implementing quality control are then determined by analyzing the causes of failures in the rope manufacturing process in order to strive for continuous improvement. The definition phase finds the four study objects with the highest error rates based on Critical to Quality (CTQ). During the measurement phase, Pareto charts are used to identify the major defect types in each process and determine the highest production variances. The DPMO probability (defects per million) is then measured and converted to sigma levels. In the analysis phase, the CTQ is analyzed with a Pareto chart and the cause and effect of the problem is analyzed with a fishbone diagram. In the improvement phase, suggestions for improvement are made. Data processing results in a DPMO value, with a Sigma level of 3.1 for the company. The main causes of defects are high engine temperatures, engine damage over time, dirty engine filters, and lack of maintenance. To manage the supply of raw materials for the ropes, he needs a form to keep his SOPs working properly.